Putrajaya smart city: a journey traces back to its past, now and near future - Chai, Hsin-Yi; Beh, Loo-See (Serbian Journal of Management, 2025)
This is the first study conducted on Putrajaya, Malaysian federal government administrative capital city, examining its ongoing second-generation smart city development which has not been conducted previously. A case study approach is used to explore the specific context of the leading role model of Malaysian smart city progress. The objectives of this study are: i) to assess the progress of Putrajaya smart city development; ii) to compare how Putrajaya fares against recommended smart city approaches; and iii) what best practices that we can learn from Putrajaya’s smart city development. The initiatives list extracted from the Putrajaya Smart City Blueprint was used as the basis and triangulated with interviews with Putrajaya local authority and town & country planners. In addition, network analysis to study multi-helix collaboration was performed using open-source software Gephi. This study found that Putrajaya smart city development progress is as per expectation in terms of initiatives execution, fares fairly well in balanced development across domains and integration of bottom-up approach in its traditional top-down administration but lagging behind in holistic strategy and multi-stakeholders collaboration. It exhibits self-sufficiency and cohesiveness of smart city initiatives which serves as the cornerstones of best practices that other cities can potentially learn from.